PERANAN SUBDIT V POLDA RIAU DALAM PENANGGULANGAN TINDAK PIDANA TERORISME MELALUIDUNIA VIRTUAL( CYBERTERRORISM ) - Jonathan Christoper Silalahi; Erdianto Erdianto; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Terrorism is a crime that is classified as special / extraordinary (extraordinary crime). Terrorism is considered a criminal act that not only harms others but also violates humanitarian principles. As the times developed, terrorism launched its actions by expanding its operations through computer networks or virtual worlds. In matters relating to the handling of criminal acts of terrorism through the virtual world, the role of law enforcement officials is needed, especially from Sub-Directorate V of the Riau Regional Police. The purpose of writing this thesis is: first, to find the obstacles of Subdit V Polda Riau in dealing with criminal acts of terrorism through the virtual world (cyberterrorism). Second, to find out the efforts of Subdit V Polda Riau in dealing with criminal acts of terrorism through the virtual world (cyberterrorism).The research method of this thesis uses a type of sociological legal research, research which is carried out by conducting legal identification and how the effectiveness of the law applies in society. This research is descriptive. Sources of data used are primary data and secondary data, which consists of primary legal materials, secondary legal materials, and tertiary legal materials. Data collection techniques in this study are using interviews and literature review, after the data is collected then analyzed to draw conclusions.From the results of research and discussion, it can be concluded that, first, in the implementation of law enforcement by Sub-Directorate V of the Riau Regional Police against criminal acts of terrorism through the virtual world (cyberterrorism), obstacles were found, namely from internal factors of Sub- Directorate V Polda Riau such as limited personnel and members who are less skilled and experienced in the field, minimal budget, infrastructure, and the presence of external factors such as conditions in the field or society as well as legal factors. Second, in the countermeasures carried out by Subdit V of the Riau Police against criminal acts of terrorism through the virtual world (cyberterrorism), namely by increasing the number of personnel or human resources, completing infrastructure and also increasing operational costs. In addition, investigators also provide appeals, counsel to the public on criminal acts of terrorism through the virtual world (cyberterrorism), form a special team to maximize surveillance that occurs in the community, and in facing obstacles from legal factors, it is necessary to harmonize law or policy formulation of laws. crimes relating to criminal acts of terrorism through the virtual world (cyberterrorism).Keywords: Sub Directorate V - Prevention - Crime of Terrorism – VirtualWorld